VD_FINDINFO Jug / 2018 / 249 vom 27. Juni 2018 - VD Tribunal cantonal (2018)
ESCROQUERIE, IN DUBIO PRO REO, ASTUCE, TROMPERIE, CONSTATATION DES FAITS, FRAIS DE LA PROCÉDURE, DÉPENS | 146 al. 1 CP, 10 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)